Automation of the design of the cross-section of the manipulator arms profile - Mihola, Milan; Zeman, Zdenek; Fojtik, David (IAES International Journal of Robotics and Automation (IJRA), 2021)
The design of the arms of industrial robots and manipulators is a demanding process both in ter ms of expertise and in terms of the time required. For these reasons, algorithms have been created, with the help of which it is possible to design cross - sections of individual arms of robots and manipulators not only from the point of view of maximum allo wed deflection but also from the point of view of minimizing cross - sectional dimensions or minimizing the weight of arms. These algorithms were subsequently used in the development of the software tool RobotArmDesign, with the help of which it is possible to simplify and shorten the arm design process significantly. This tool also has a connection to the SolidWorks CAD system and its simulation tools through its API interface, making it possible to refine robot arms designs while maintaining significantly s horter design times than would be the case with commonly used procedures. This tool's capabilities were demonstrated in the design of a robot arm with an angular structure and five degrees of freedom.